2015
DOI: 10.1589/jpts.27.585
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training in modulation of aerobic physical fitness and balance of burned patients

Abstract: [Purpose] This study aimed to determine the impact of aerobic exercise on aerobic capacity, balance, and treadmill time in patients with thermal burn injury. [Subjects and Methods] Burned adult patients, aged 20–40 years (n=30), from both sexes, with second degree thermal burn injuries covering 20–40% of the total body surface area (TBSA), were enrolled in this trial for 3 months. Patients were randomly divided into; group A (n=15), which performed an aerobic exercise program 3 days/week for 60 min and partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…The current study indicates that any exercise training, whether it is categorized as aerobic, strength or combining both aerobic and strength (concurrent), conducted 3 times per week for eight weeks, with moderate intensity is proven to reduce waist circumference. Many previous studies have suggested that aerobic exercise is the best type of exercise for total body fat loss (both visceral and subcutaneous adipose tissue) including for the abdominal region (Ali, El-Refay, & Ali, 2015;Okura, Nakata, Lee, Ohkawara, & Tanaka, 2005). However, this is contradicted by the results gathered in this study which surprisingly showed strength training group demonstrated greatest improvement in waist circumference based on the magnitude of changes as reported in results compared to other intervention groups.…”
Section: Discussioncontrasting
confidence: 80%
“…The current study indicates that any exercise training, whether it is categorized as aerobic, strength or combining both aerobic and strength (concurrent), conducted 3 times per week for eight weeks, with moderate intensity is proven to reduce waist circumference. Many previous studies have suggested that aerobic exercise is the best type of exercise for total body fat loss (both visceral and subcutaneous adipose tissue) including for the abdominal region (Ali, El-Refay, & Ali, 2015;Okura, Nakata, Lee, Ohkawara, & Tanaka, 2005). However, this is contradicted by the results gathered in this study which surprisingly showed strength training group demonstrated greatest improvement in waist circumference based on the magnitude of changes as reported in results compared to other intervention groups.…”
Section: Discussioncontrasting
confidence: 80%
“…Many previous studies have suggested that aerobics and brisk walking are the best methods for weight reduction 19 , 20 , 29 ) . The difference between obesity and overweight is defined by the BMI.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 studies [22][23][24][27][28][29][30][31][32][33][34][35][36][37]39 reported outcomes in children and 4 involved adults exclusively. 21,25,26,38 All 19 trials were performed in hospital settings with 12 performed in the same pediatric burn research center in Galveston, USA. Time postburns also differed among included studies.…”
Section: Demographics and Settingmentioning
confidence: 99%
“…Of the 17 RCTs included, just 5 [23][24][25][26][27] explicitly reported the randomization method and 4 [25][26][27]29 reported the allocation concealment process. Only seven randomized trials 21,[23][24][25][26][27]32 had four or more items (out of seven items) scored as "low risk of bias" (Supplementary File 3).…”
Section: Quality Assessment: Within Studiesmentioning
confidence: 99%